Information needs of cancer patients and its impact on patient outcomes - Salek, S; Al-Mohammadi, A; Nicholls, P; Maughan, T; Mason, M (2005)
The objective of the study was to assess cancer patients' needs for information and its impact on related outcomes and improvement of cancer care. The study was prospective and cross-sectional using a self-administered questionnaire technique, the Patient Communication Questionnaire (PCQ). The study took place at the outpatient, inpatient and day care unit of Velindre NHS Trust Hospital, Cardiff, United Kingdom. The PCQ consists of seven sections assessing a patient's needs for information and outcomes such as understanding, satisfaction and the patient's mental distress. In addition, a single question identifies how much of an active role the patient wants to play in treatment decision-making. A total of 100 patients completed the PCQ (26 male; median age = 59, age range = 28-80 years). It was found that the majority of patients preferred to participate in their treatment decisions. Women with breast cancer were most likely to prefer to be involved. Those patients who wanted to participate in the decision-making process scored higher in their needs for information; preferred to receive additional written materials; were less satisfied with the quality of information given; and expressed higher mental distress. Low patient satisfaction was associated with the amount of information given by specialist pharmacists; with the level of information regarding their prognosis; their ability to express their feelings; and their feeling of not being given all the information. Patients who felt they had been given honest information, were highly informed, reassured, involved in treatment decisions and whose treatments were explained well, reported better outcomes. The correlation coefficients between the PCQ sub-scales indicated that it is the quality, rather than the quantity of the information given that tends to affect patient outcomes.